(untitled) (Papeles, 2018)
The following article is derived from a research, in which was sought to determine whether the “Ley ProJoven” (ProJoven Law) really works at the moment of hiring young people. For that, both private enterprises and public entities were surveyed, and it was analyzed the variation produced in the youth unemployment rate since 2007 to 2018, emphasizing the period between the publishing of the Law and 2018, so in this way we could stablish if it had any effect over the decrease of youth unemployment.